Counterintelligence for Corporate Environments, Volume II : How to Protect Information and Business Integrity in the Modern World. - Van Genderen, Dylan (Business Law and Corporate Risk Management Collection,, 2018)
Counterintelligence for Corporate Environments, Volume II discusses topics and illustrates strategies and procedures that have never before been used in the corporate field. Inspired by the concepts, strategies, and tactics that have been used by intelligence communities and specialized military forces for decades, this book aims to improve and safeguard every component of a corporate environment through the adaptation and modification of the same strategies employed by these specialized entities. Through this book, managers, security officers, consultants, and entire corporate environments will have the knowledge and skills necessary in order to change the entire dynamic of security applications in the present day and will be able to integrate advanced and highly efficient counterintelligence models in order to combat the extensive modern threat landscape.